2019
DOI: 10.1002/mame.201800763
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of C/C‐SiC Composites from All‐Cellulose Precursors

Abstract: All‐cellulose composites (ACCs) are manufactured from high‐performance cellulose fibers and a cellulose‐containing ionic liquid (IL) as matrix‐forming dope via wet‐winding processes, using different concentrations of cellulose in the IL. ACCs are carbonized at 1650 °C and then infiltrated with liquid silicon. Application of a carbonization aid (ammonium dihydrogenphosphate, ADHP) substantially improves the carbon yield after carbonization but also results in the depletion of the mechanical properties of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Such new developments were highlighted in a review by Hermanutz et al [ 146 ] Interesting technical applications such as all‐cellulose composites, spinning of polymer blends (e.g., cellulose plus chitin) and precursors for carbon fibers were described. [ 147 ] For carbon fiber precursors, it was shown that the use of different ILs makes it possible to co‐spin lignin (another abundant renewable wood‐based macromolecule) with cellulose. This can result in an increased yield of the final carbon fiber as well as reduced processing time during the stabilization step of the conversion to carbon fibers.…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…Such new developments were highlighted in a review by Hermanutz et al [ 146 ] Interesting technical applications such as all‐cellulose composites, spinning of polymer blends (e.g., cellulose plus chitin) and precursors for carbon fibers were described. [ 147 ] For carbon fiber precursors, it was shown that the use of different ILs makes it possible to co‐spin lignin (another abundant renewable wood‐based macromolecule) with cellulose. This can result in an increased yield of the final carbon fiber as well as reduced processing time during the stabilization step of the conversion to carbon fibers.…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…While most publications describe the production of staple fibers suitable for use in the textile industry, the use of cellulosic fibers is by far not limited to these applications, the mores since special viscose fibers are used as tire cord fibers and as reinforcement fibers for composites (Schneck et al 2019;Spörl et al 2017a;Wooding 1995;Zadorecki et al 1986). In this study we present an IL-based spinning process that allows for the production of endless multi-filament fibers with properties comparable to those of commercial tire cord fibers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–14 ] Consequently, alternative precursor materials and processes are highly needed. Current research focuses on alternative precursors from low‐cost, renewable resources such as cellulose [ 15–20 ] or lignin. [ 21–32 ] Alternatively, melt spinnable PAN copolymers have again moved into the center of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a PAN‐based CF process, almost 60% of the costs can be saved in precursor synthesis. [ 5 ] Another outstanding property of PE is its very high theoretical carbon yield of 85 wt%, which exceeds the one of other CF precursors such as cellulose (44 wt%) [ 15–20 ] or lignin (< 65 wt%). [ 21–32,38 ] And indeed, carbon yields from PE precursors of up to 76 wt% have been reported.…”
Section: Introductionmentioning
confidence: 99%